Fiscal Transparency, Borrowing Costs, and Foreign Holdings of Sovereign Debt - Kemoe, Laurent (IMF Working Papers; Working Paper ;, 2018)
This paper explores the effects of fiscal transparency on the borrowing costs of 33 emerging and developing economies (EMs), and on foreign demand for their sovereign debt. Using multiple indicators, including a constructed one based on the published data in the IMF's Government Finance Statistics Yearbook, we measure the separate effects of the three dimensions of fiscal transparency: openness of the budget process, fiscal data transparency, and accountability of fiscal actors. The results suggest that higher fiscal transparency reduces sovereign interest rate spreads and increases foreign holdings of sovereign debt, with each dimension of fiscal transparency playing a different role. Availability of detailed cross-country comparable fiscal data, especially for balance sheet items, has shown to increase foreign investors' willingness in holding EM sovereign debt.